2006
DOI: 10.1053/j.gastro.2006.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Multiple Drug-Resistant Hepatitis B Virus Strain in a Liver-Transplanted Patient

Abstract: Background & Aims: Sequential anti-HBV therapy may lead to the selection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
2
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 36 publications
8
132
2
3
Order By: Relevance
“…Previous in vitro studies have shown that ADV-resistant HBV strains were susceptible to ETV. [17][18][19] Although increasing evidence supports the therapeutic efficacy of ETV in LAMr patients, [13][14][15] limited clinical data are available on ADV-resistant patients showing prior LAM resistance. 20,21 A small cohort study showed that switching to ETV plus ADV was highly efficient in 13 CHB patients who failed sequential or combination therapy with LAM and ADV, with a 76.9% (10/13) HBV DNA clearance rate during a median 10 months of treatment (range, 4-16 months).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have shown that ADV-resistant HBV strains were susceptible to ETV. [17][18][19] Although increasing evidence supports the therapeutic efficacy of ETV in LAMr patients, [13][14][15] limited clinical data are available on ADV-resistant patients showing prior LAM resistance. 20,21 A small cohort study showed that switching to ETV plus ADV was highly efficient in 13 CHB patients who failed sequential or combination therapy with LAM and ADV, with a 76.9% (10/13) HBV DNA clearance rate during a median 10 months of treatment (range, 4-16 months).…”
Section: Discussionmentioning
confidence: 99%
“…38,54 Isolates of HBV with rtN236T and rtA181V changes are susceptible to entecavir in vitro. 39,48,56 Case reports have confirmed the in vivo efficacy of lamivudine and entecavir in the suppression of adefovir resistant HBV. 39,55,57 Tenofovir (TDF) -There was a recent report of resistance to TDF associated with HBV encoding changes in HBV polymerase at rtL180M ϩ rtA194T (alanine to threonine substitution) ϩ rtM204V in 2 HIV / HBV co-infected patients.…”
Section: (A) Resistance To Monotherapiesmentioning
confidence: 91%
“…60 Recent studies reported that multidrug resistance changes can be detected in patients who received sequential NA monotherapy and clonal analysis showed that in most instances, the mutations associated with both treatments reside in the same clone. 56,60 The collocation of mutations associated with resistance to different treatments on the same genome is worrisome because in vitro analysis of antiviral sensitivities revealed that replicating clones with LAM and ADV-associated mutations had Ͼ50-fold reduced susceptibility to combination of LAM and ADV indicating that combination therapy of the 2 drugs may not be effective in suppressing multidrug resistant HBV. 54,56…”
Section: (B) Multidrug Resistancementioning
confidence: 99%
“…On the other hand, higher occurrence of resistance have been reported following monotherapy with either HBIg (0% to 71%) or NA (lamivudine) (0% to 39.7%) [74,75] (Table 1). Further, multiple drug/HBIg variants have been reported in patients receiving both interventions (especially in combination with lamivudine) [72,73,76,77] . Obviously with current new NA agents like adefovir, entecavir, tenofovir, etc, the recurrence rate decreased to 0% to 12.9% (Tables 1-3 …”
Section: Pre-lt Hbv Dna Levels A: Early Recurrencementioning
confidence: 99%